An Analysis of the Impact of Web Series in Shaping Consumer Preferences: A Case Study of the South Korean Drama Series Hospital Playlist - Sitorus, Nanda Trecya; Riadi, Selamat (Holistic Science, 2025)
The development of digital technology has changed media consumption patterns, presenting opportunities for web series to shape consumer preferences. Hospital Playlist, a Korean drama with a realistic narrative and humanitarian values, is a successful example of combining quality content and creative marketing strategies. This study aims to analyze the impact of web series on shaping consumer preferences through a case study of Hospital Playlist. The method used was a qualitative case study approach, involving in-depth interviews, social media observation, and content analysis. Informants were selected through purposive sampling with the criteria of having watched at least one season of Hospital Playlist and actively discussing it on social media. The results show that emotional engagement is a dominant factor in shaping preferences, supported by authentic storytelling, authentic characters, and appropriate background music. Cross-platform marketing strategies, including the use of social media and a partnership with Netflix, expanded reach and strengthened audience loyalty. These findings confirm that the combination of a strong narrative, integrated distribution, and emotional engagement is effective in building and maintaining audience interest. In conclusion, Hospital Playlist has successfully become a model for digital entertainment content strategies that are able to shape consumer preferences through an emotional approach and creative marketing, providing important implications for the development of mass communication theory and entertainment industry practice.